Screening of cryptic species among clinical Aspergillus isolates collected during one year period in a Portuguese reference laboratory - Sabino, R. (2014)
Objectives: Correct identification of Aspergillus species is important given that sibling species may show variable susceptibilities to multiple antifungal drugs and also because sharper definition of species may facilitate epidemiological studies. Thus, we screened Aspergillus clinical isolates from Portuguese hospitals to determine which, if any, of the cryptic species of Aspergillus were involved in patient infections. Methods: Over a one year period, Aspergillus isolates from Portuguese health institutions were collected. These isolates were identified on the basis of microscopic morphology and through the use of molecular tools. Genomic DNA was prepared from each isolate and the sequencing of the Internal Transcribed Spacers (ITS) regions, specifically the ITS1 and ITS2 non-coding regions flanking the 5.8S rDNA was used to determine the species complex, whereas β-tubulin and calmodulin sequencing was done to achieve the correct species identification. Results: Over the study period, 57 Aspergillus isolates from clinical samples were collected from 10 Portuguese health institutions. According to the morphological observations, 29 isolates were identified as Aspergillus fumigatus, 11 A. flavus, 8 A. niger, 3 A. nidulans, 2 A. terreus, 2 A. candidus and 2 Aspergillus sp. Among those isolates, six species-complexes were detected by ITS sequencing, and were distributed as follows: fumigati (50.1%), flavi (21.0%), nigri (15.8%), terrei (5.3%), nidulantes (3.6%) and versicolores (3.6%). β-tubulin and calmodulin sequencing resulted in ten (17.5%) cryptic species being identified among the 57 isolates. Six of those isolates belonged to the nigri complex (A. brasiliensis, A. awamorii and A. tubigensis), two to the versicolores complex (A. sidowii and A. fructus), one to the fumigati complex (A. lentulus) and one to the nidulantes complex (Emmericella echinulata). Conclusion: With rigorous application of molecular tools, cryptic species of Aspergillus are not uncommon in the clinic. The identification of cryptic species among the collected clinical isolates of Aspergillus alerts the clinician to isolates with reduced susceptibilities to antifungal drugs and emphasizes a correct identification to species level.